Draft genome sequences of six Enterococcus faecalis strains isolated from Malaysian clinical and environmental origins - Daniel, D.; Gan, H.; Lee, S.; Dykes, Gary; Rahman, S. (American Society for Microbiology, 2017)
© 2017 Daniel et al. Enterococcus faecalis is known to cause a variety of nosocomial infections, including urinary tract infections. Antibiotic resistance and virulence properties in this species are of public concern. The draft genome sequences of six E. faecalis strains isolated from clinical and environmental sources in Malaysia are presented here.